2013
DOI: 10.1242/jcs.111658
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat protein inhibits neurosecretion by binding to phosphatidylinositol 4,5-bisphosphate

Abstract: Summary HIV-1 transcriptional activator (Tat) enables viral transcription and is also actively released by infected cells. Extracellular Tat can enter uninfected cells and affect some cellular functions. Here, we examine the effects of Tat protein on the secretory activity of neuroendocrine cells. When added to the culture medium of chromaffin and PC12 cells, Tat was actively internalized and strongly impaired exocytosis as measured by carbon fiber amperometry and growth hormone release assay. Expression of Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…In neurosecretory cells, it has been proposed that Tat perturbs the recruitment of several PIP 2 -dependent key players of the exocytotic machinery [32]. Combined with this previous investigation, our work suggests a general remodeling of PIP 2 -dependent processes by HIV via Tat.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…In neurosecretory cells, it has been proposed that Tat perturbs the recruitment of several PIP 2 -dependent key players of the exocytotic machinery [32]. Combined with this previous investigation, our work suggests a general remodeling of PIP 2 -dependent processes by HIV via Tat.…”
supporting
confidence: 79%
“…cotransfection of hERG with either WT-or W11Y-Tat/GFP bidirectional plasmids. They confirmed that WT-Tat localizes at the COS-7 plasma membrane, through its interaction with PIP 2 [32]. Unlike WT-Tat, W11Y-Tat localized diffusely in the cytosol, its lack of affinity for PIP 2 preventing its plasma membrane localization ( Figure 3A & B).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…It should be noted that Tat targets in these biological systems are different, Annexin A2 (ref. 54) for neurons/exocytosis and Cdc42 (this study) for macrophages/ phagocytosis. The capacity of Tat to perturb these activities is also different since subnanomolar concentrations of Tat are sufficient to efficiently inhibit phagocytosis, while 5-10 nM of Tat are required to affect the neurosecretory activity 54 .…”
Section: Discussionmentioning
confidence: 68%
“…Tat is an original toxin in this field since it affects Cdc42 function by preventing its recruitment to the phagocytic cup, thereby preventing its activation. Hence, Tat is a PI(4,5)P 2 targeting toxin that can affect the neurosecretory 54 , the phagocytic (this study) and probably other PI(4,5)P 2 -dependent membrane traffic machineries. It should be noted that Tat targets in these biological systems are different, Annexin A2 (ref.…”
Section: Discussionmentioning
confidence: 86%